Russell and Wittgenstein: apprenticeship and other ‘crossings’ - V. V. Tselishchev (Омский научный вестник: Серия "Общество. История. Современность")
The article is devoted to the analysis of the traditional interpretation for the development of personal and intellectual relations between Russell and Wittgenstein in the light of the publication of materials from the Russell Archive. The mythology of the traditional interpretation of the development and collaboration of Wittgenstein and Russell is demonstrated and criticized. A more complex trajectory of the development of these relations is shown, which does not correspond to the traditional interpretation, according to which this development led to a kind of intellectual and creative surrender of Russell to his former student.